Modulation of miRNAs by protein intake: A novel approach to mitigating stunting in children - Tonny Sundjaya; Ray Wagiu Basrowi; Dessy Pratiwi; Nurlinah Amalia; Ariq Fadhil Athallah; Maulana Bagus Adi Cahyono; Caesaroy Afif Wibowo; Fahrul Nurkolis (Journal of Agriculture and Food Research)
MicroRNAs (miRNAs) are small, non-coding RNA sequences that have a pivotal role in regulating gene expression, thereby influencing a range of biological processes, including growth and development. One of the retardation growth and development is stunting, refers to inadequate linear growth during a critical developmental period. A deeper understanding of miRNA mechanisms in stunting, especially the relationship between miRNA and protein intake, could provide valuable insights for developing interventions to improve child growth outcomes. The majority of several studies demonstrate that various types of miRNAs influence growth hormone by downregulating its expression. Previous research has highlighted the potential of miRNA targeting in the management of stunting; however, the number of studies in this area remains limited.